Evaluation of implant success: A review of past and present concepts - Kaneesh Karthik; Sivakumar; Sivaraj; Vinod Thangaswamy (Wolters Kluwer Medknow Publications, 2013)
Dental Implants have become the standard care of rehabilitation of missing teeth. This article intends to review the success criteria for implants from 1979 till date. Earlier days implant success was evaluated by immobility and peri-implant radiolucency. But currently, the width of the attached gingiva, co-existing medical conditions, smoking, and width of the implant also play a role in evaluating implant success. Genetic and immunological markers have also been identified.